Conversion to Islam and the right of child custody in Selangor / Muhamad Wazir Muslat. - Muslat, Muhamad Wazir (2010)
This study is about conversion to Islam and the right of child custody with special reference to the State of Selangor. The issues relating to conversion to Islam, especially those cases pertaining to the right of custody of the minors have led to tension and have been given a wide coverage both locally and internationally. Furthermore, since the court system in Malaysia has a dual system between Muslims and non-Muslims, conflict of laws and jurisdiction have often occurred as the Muslim party cannot defend his/her right before the Civil Court and as for the non-Muslim party before the Syariah Court. Therefore, this study seeks to examine the issues and offer a relevant resolution as there are many pending cases which involved the disagreement claim of minor child custody among persons converted to Islam while his or her spouse refused to do so. As a result, conflict of laws between the Syariah and Civil laws and cases involving custody have never come to an end. At the end of the study, suggestion has been made to amend and add some provisions in both Civil and Syariah laws as there is a lacuna in the present laws.